2018
DOI: 10.1007/s11548-018-1787-6
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted liver graft steatosis assessment via learning-based texture analysis

Abstract: Purpose Fast and accurate graft hepaticsteatosis (HS) assessment is of primary importance for lowering liver-dysfunction risks after transplantation. Histopathological analysis of biopsied liver is the goldstandard for assessing HS, despite being invasive and time consuming. Due to the short time availability between liver procurement and transplantation, surgeons perform HS assessment through clinical evaluation (medical history, blood tests) and liver-texture visual analysis. Despite visual analysis being re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…This may be attributed to the ability of the SVM of handling high-dimensional feature-space (which was high if compared with the number of subjects in the LDV-beat dataset) and its robustness of tackling the noise components of the LDV signal. Similar conclusions have already been drawn in closer research fields [ 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 88%
“…This may be attributed to the ability of the SVM of handling high-dimensional feature-space (which was high if compared with the number of subjects in the LDV-beat dataset) and its robustness of tackling the noise components of the LDV signal. Similar conclusions have already been drawn in closer research fields [ 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, the inclusion of donor features in the algorithm helped increase the Acc of the classification by SVM‐SIL, as previously demonstrated. ( 14 ) The real innovation of this study, through AI computerization of a human process, is 3‐fold: first, to translate the subjective visual assessment of liver texture into an objective and standardized method (smartphone picture); second, to develop a fully automated HS assessment by the liver graft image extraction; and third, to replicate the clinical experience of a transplant surgeon (donor data analysis). A major limitation of this study is the small sample size, which is a common problem within the computer‐assisted diagnosis community, ( 20 ) particularly in the LT setting wherein a larger cohort of discarded grafts (without any intention to be transplanted) are available only for machine perfusion studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study ( 14 ) a set of images was created by manually cropping the original photographs so the target organ (liver) would occupy 100% of the frame with elimination of the background. Contrary to this method, in this study, a FCNN was used that was composed of several layers as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Textural features include local binary pattern [43], gray-level co-occurrence matrix [44], and histogram of oriented gradients [45]. This class of features has been successfully used for several applications, such as tissue classification in gastric [46] and colorectal images [47,48].…”
Section: Semantic Segmentationmentioning
confidence: 99%